Synthesis and Luminescence Property of Red Phosphor CaMoO4:Eu3+ via Sol-Gel Method - Zhang, Jianfu; Wang, Jun; Bu, Shoukun; Wang, Zhenling (Asian Journal of Chemistry, 2014)
Red phoshors played an important role on optimizing the LED white light chromaticeness. CaMoO4:Eu3+ was synthesized by sol-gel method, which was characterize by X-ray powder diffraction, scanning electron microscope and photoluminescence spectra. The results showed that CaMoO4:Eu3+ (5 %, mass ratio) prepared in pH value of 7-11 and calcined at 700 °C became uniformly cubic crystal and exhibited red photoluminescence with strongest emission peak at 612 by 258 nm excitation, which was caused by 5D0®7F2 transition of Eu3+.